Optimization of the electrode drive pattern for imaging fascicular compound action potentials in peripheral nerve with fast neural Electrical Impedance Tomography (EIT) - Ravagli, Enrico (Physiol Meas, 2019)
OBJECTIVE: The main objective of this study was to investigate which injection pattern led to the best imaging of fascicular compound activity in fast neural EIT of peripheral nerve using an external cylindrical 2x14-electrodes cuff. Specifically, the study addressed the identification of the optimal injection pattern and of the optimal region of the reconstructed volume to image fascicles. APPROACH: The effect of three different measurement protocol features (transversal/longitudinal injection, drive electrode spacing, referencing configuration) over imaging was investigated in simulation with the use of realistic impedance changes and noise levels. Image-based metrics were employed to evaluate the quality of the reconstructions over the reconstruction domain. The optimal electrode addressing protocol suggested by the simulations was validated in vivo on the tibial and peroneal fascicles of rat sciatic peripheral nerves (N=3) against MicroCT reference images. MAIN RESULTS: Injecting current transversally, with spacing of ≥4 electrodes apart (≥100°) and single-ring referencing of measurements, led to the best overall localization when reconstructing on the edge of the electrode array closest to the reference. Longitudinal injection protocols led to a higher SNR of the reconstructed image but poorer localization. All in vivo EIT recordings had statistically significant impedance variations (p<0.05). Overall, fascicle center-of-mass (CoM) localization error was estimated at 141±56μm (−26±94μm and 5±29° in radial coordinates). Significant difference was found (p<0.05) between mean angular location of the tibial and peroneal CoMs. SIGNIFICANCE: This study gives the reader recommendations for performing fast neural EIT of fascicular compound activity using the most effective protocol features.